Insulin Promoter Factor 1 variation is associated with type 2 diabetes in African Americans - Wang Xiaoqin; Karim Mohammad A; Hale Terri C; Elbein Steven C (BMC, 2005)
Abstract Background Defective insulin secretion is a key defect in the pathogenesis of type 2 diabetes (T2DM). The β-cell specific transcription factor, insulin promoter factor 1 gene (IPF1), is essential to pancreatic development and the maintenance of β-cell mass. We hypothesized that regulatory or coding variants in IPF1 contribute to defective insulin secretion and thus T2DM. Methods We screened 71 Caucasian and 69 African American individuals for genetic variants in the promoter region, three highly conserved upstream regulatory sequences (PH1, PH2 and PH3), the human β-cell specific enhancer, and the two exons with adjacent introns. We tested for an association of each variant with T2DM Caucasians (192 cases and 192 controls) and African Americans (341 cases and 186 controls). Results We identified 8 variants in the two populations, including a 3 bp insertion in exon 2 (InsCCG243) in African Americans that resulted in an in-frame proline insertion in the transactivation domain. No variant was associated with T2DM in Caucasians, but polymorphisms at -3766 in the human β-cell enhancer, at -2877 bp in the PH1 domain, and at -108 bp in the promoter region were associated with T2DM in African American subjects (p < 0.01), both individually and as haplotypes (p = 0.01 correcting by permutation test). No SNP altered a binding site for the expected β-cell transcription factors. The rare alleles of InsCCG243 in exon 2 showed a trend to over-representation among African American diabetic subjects (p < 0.1), but this trend was not significant on permutation test. Conculsion The common alleles of regulatory variants in the 5' enhancer and promoter regions of the IPF1 gene increase susceptibility to type 2 diabetes among African American individuals, likely as a result of gene-gene or gene-environment interactions. In contrast, IPF1 is not a cause of type 2 diabetes in Caucasians. A previously described InsCCG243 variant may contribute to diabetes susceptibility in African American individuals, but is of low penetrance.